Effects of canagliflozin on myocardial microvascular density, oxidative stress, and proteomic profile - Sharif A. Sabe; Cynthia M. Xu; Mohamed Sabra; Dwight D. Harris; Mark Broadwin; Krishna G. Bellam; Debolina Banerjee; Anny Usheva; M. Ruhul Abid; Frank W. Sellke (Journal of Molecular and Cellular Cardiology Plus, 2023)
Introduction: Sodium-glucose cotransporter-2 inhibitors (SGLT2i) are cardioprotective, and canagliflozin (CANA), an SGLT2i, has been shown to improve perfusion, AMPK signaling, and oxidative stress in chronically ischemic myocardium. The aim of this study is to determine the effects of CANA in nonischemic myocardium on coronary collateralization, oxidative stress, and other molecular pathways determined by proteomic profiling. Methods: Yorkshire swine underwent placement of an ameroid constrictor to the left circumflex artery. Two weeks later, pigs received no drug (CON, n = 8) or 300 mg CANA daily (n = 8). Treatment continued for five weeks, followed by tissue harvest of nonischemic myocardium. Results: CANA was associated with decreased capillary density (p = 0.05) compared to CON, without changes in arteriolar density. Reduced capillary density did not correlate with reduced perfusion. Oxidative stress was reduced with CANA (22 % decrease). In the CANA group, there was a trend towards increased p-eNOS and eNOS, without a change in p-eNOS/eNOS ratio, p-Akt, Akt, and p-Akt/Akt ratio. There was no change in p-ERK1/2, but a decrease in total ERK1/2 and increase in p-ERK1/2/ERK1/2 ratio. There were no changes in expression of p-AMPK, AMPK, with a trend towards increased ratio of p-AMPK/AMPK. Proteomics analysis identified 2819 common proteins, of which 120 were upregulated and 425 were downregulated with CANA. Pathway analysis demonstrated wide regulation of metabolic proteins. Conclusions: The effects of CANA on myocardial perfusion and AMPK signaling in chronically ischemic myocardium are not found in nonischemic territory, despite attenuation of oxidative stress. Metabolic proteins are widely regulated in nonischemic myocardium with CANA.